Socio-demographic profile of poisoning in children admitted to a tertiary hospital - Srinivasa, B S; Manuprakash, S K; Ara, Syeda Saltanat; Kumar, S R; Prasannakumar, D G (Indian Journal of Child Health, 2016)
Background: Childhood poisoning is a significant public health problem and is very important cause of mortality and morbidity in children. The offending substances used vary from place to place. The pattern of poisoning has been changing with new hazards constantly appearing due to the introduction of new drugs and chemicals. Childhood poisoning is usually accidental making poisoning a preventable problem. Objectives: To determine the socio-demographic and clinical profile and outcome of childhood poisoning in a tertiary care hospital. Materials and Methods: This prospective study was done over a period of 2-year in a tertiarycare hospital. We studied children